PENGELOLAAN FASILITAS AGROWISATA SIGARAN JIWA DI KAMPUNG JAYAPURA KABUPATEN SIAK - Nawawi, Ahmad; Fitriani, Febri; Andri Wibowo (Puslitabmas Batam Tourism Polytecnic, 2024)
This study aims to analyze the management of facilities at Sigaran Jiwa Agrotourism, located in Kampung Jayapura, Siak Regency, which has emerged as a significant destination within the region, particularly following the post-COVID-19 recovery. Sigaran Jiwa Agrotourism is centered around agricultural-based tourism activities and has witnessed a steady increase in visitors, drawing interest for its unique blend of nature and agro-education experiences. This research employs a qualitative approach, gathering data through a combination of field observations, in-depth interviews with key stakeholders, including site managers, staff, and visitors, as well as reviewing relevant secondary sources such as financial and maintenance reports. The findings reveal that, while the number of visitors has consistently increased from 2020 to 2023, the site’s facility management is currently facing several challenges related to the upkeep and further development of essential infrastructure. Notably, certain facilities, such as gazebos, observation towers, and playgrounds, are well-maintained and contribute to the positive visitor experience. However, other critical areas, such as parking spaces, toilets, and accessibility for the disabled, require significant improvement to meet growing demand and enhance visitor satisfaction. The study concludes that, with strategic improvements in facility management and stronger support from local authorities and stakeholders, Sigaran Jiwa Agrotourism holds great potential to further develop into a leading and sustainable tourism destination within Siak Regency, contributing not only to local economic growth but also promoting eco-friendly tourism practices.